ANALYSIS OF ROAD CONDITION VALUE ON THE NATIONAL ROAD TEUKU UMAR TUBAN USING BINA MARGA METHOD - Richo Ardidarmawan Mintiya; Herry Widhiarto; Aditya Rizkiardi (Jurnal Penelitian)
Roads are the most important aspects of distribution, social, and economic fields, but over time and changing weather is often the cause of road damage. Therefore, it is necessary to have a review carried out to be able to determine the type of damage and the degree of damage that occurs. Observations will be made on the Teuku Umar Tuban Road Section by referring to the Bina Marga Method. Observations will be carried out visually and only analyzed only on the surface, in addition to calculating the daily vehicle volume. From the observation process, types of damage were obtained, namely patholes, cracking, patchng, depression and rutting. Based on the type of damage, repairs will be carried out on the most numerous and fundamental type of damage is to use the crack fill method, this is done because this road has a crack of 55%.